The EFFECT OF INSTAGRAM SOCIAL MEDIA MARKETING ACTIVITIES ON REVISIT INTENTION TO KOPI COMPLEKS SURABAYA WITH CONSUMER ENGAGEMENT MEDIATION - Alfarrel Fathan Hendrawan; Monika Tiarawati (Jurnal Ilmu Manajemen, 2026)
This study examines the effect of Instagram social media marketing activities on revisit intention to Kopi Kompleks Surabaya, with consumer engagement as a mediating variable. Despite the increasing use of Instagram by local coffee shops, the effectiveness of social media marketing in driving consistent revisit behavior remains inconsistent, indicating a gap between digital promotion and consumer loyalty. This study addresses this gap by incorporating consumer engagement as a mediating mechanism within the online-to-offline (O2O) context. A quantitative explanatory approach was employed using a cross-sectional survey of 200 respondents who have visited Kopi Kompleks and interacted with its Instagram account. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that Instagram marketing activities significantly influence both consumer engagement and revisit intention. Consumer engagement also has a significant effect on revisit intention and partially mediates the relationship between social media marketing and revisit intention. This study contributes to the digital marketing literature by highlighting the mediating role of consumer engagement in strengthening the effectiveness of social media strategies for local coffee shops.